2022
DOI: 10.3390/molecules27206816
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of N-Rich Porous Carbon for Efficient CO2 Adsorption Performance

Abstract: N-enriched porous carbons have played an important part in CO2 adsorption application thanks to their abundant porosity, high stability and tailorable surface properties while still suffering from a non-efficient and high-cost synthesis method. Herein, a series of N-doped porous carbons were prepared by a facile one-pot KOH activating strategy from commercial urea formaldehyde resin (UF). The textural properties and nitrogen content of the N-doped carbons were carefully controlled by the activating temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…It can therefore be concluded from the overall results that the combination of textural features and suitable nitrogen functionality on carbon materials contributes to a positive effect on CO 2 uptake capacity than the effect of single textural properties. A similar phenomenon was previously reported in the literature [ 75 , 76 ].
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…It can therefore be concluded from the overall results that the combination of textural features and suitable nitrogen functionality on carbon materials contributes to a positive effect on CO 2 uptake capacity than the effect of single textural properties. A similar phenomenon was previously reported in the literature [ 75 , 76 ].
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…It is interesting to underline that the highest CO 2 adsorption capabilities discovered in this inquiry are noticeably lower than those reported for some KOH-activated porous nanocarbons, as shown by earlier investigations, , However, they demonstrate equivalent or even greater adsorption values when compared with particular carbon materials and various other standard CO 2 adsorbents, including COFs, porous polymers, and MOFs . A complete comparison of the uptake of CO 2 among SDC carbons and other solid sorbents is presented in Table S2 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 52%
“…As shown in Figure 3 a and Figure S1a , all samples had two broad diffraction peaks at 26.5° and 44.5°. By comparing with the standard card of graphite (JCPDS card No.01-0640), it can be observed that the peak at 26.5° corresponds to the (002) non-crystalline carbon of graphite, and the weak diffraction peak at 44.5° corresponds to (101), further indicating its degree of graphitization [ 37 ]. Therefore, these samples have a low degree of graphitization and exhibit a non-crystalline carbon structure, and this amorphous structure could promote the transport of charged ions [ 38 ].…”
Section: Resultsmentioning
confidence: 99%